Fatores de risco para a tentativa de suicídio em um hospital de referência da mesorregião noroeste do ceará: estudo caso-controle - Félix, Tamires Alexandre (2016)
Suicide attempts can be conceptualized as intentional self-harm acts that do not result in death. In Brazil, more than 30 self-induced deaths were registered per day in 2012, wherein the estimate of suicide attempts tends to be 10 to 20 times higher, impacting greatly on family life. In the health region of Sobral – Ceará, rates have been progressively increasing without the respective intervention from management to prevent new cases and monitor risk groups. The objective of this study was to analyze the association of risk factors with suicide attempts in people treated at a referral hospital in Sobral using the case-control method. In this manner, it contributes to the characterization of demand, quality of care, monitoring and evaluation in the context of Primary Health Care, and especially in intersectoral preventive actions. This is a population-based, case-control study with quantitative approach conducted in the adult emergency department of the Santa Casa de Misericórdia de Sobral Hospital, a service hub for the Northwest Mesoregion. One hundred and fifty-three cases and 153 controls admitted between August 2013 and August 2015 were matched for sex, age and origin. Data collection was conducted by means of a questionnaire, and the information was processed with the Statistical Package for Social Sciences software and analyzed using descriptive statistics. The study followed Resolution 466/12 with approval from the Ethics Committee of the State University Vale do Acaraú (#384,646). There was an average of 1.47 attempted suicides admitted per week made up predominantly of young adults with no significant differences for gender. The predominant method was Exogenous Poisoning and the most mentioned motivations were love and family conflicts. Most cases presented good clinical evolution and were discharged in less than 48 hours. The practice of leisure activities has been shown as a protective factor reducing in approximately 80% the risk of a suicide attempt. Risk factors with statistical significance were ‘previous suicide attempt’, ‘suffering from some kind of mental health disorder’, ‘family history of self-injury behavior’ and ‘drug abuse/addiction’. Many of the controls also mentioned risk context and reported suicidal thoughts at some point in life. Proposals were presented to the Mental Health Network of Sobral from the obtained results. Thus, identified from the most impacting predictors, awareness notification, and implementation of the proposal from the Multidisciplinary Group of Suicide Attempt Prevention constitute aspects for the upgrading and strengthening of municipal policy.